COMBINATION OF PRENATAL GENTLE YOGA EXERCISES AND LAVENDER AROMATERAPY INHALATION TO IMPROVING SLEEP QUALITY IN TRIMESTER III PREGNANT WOMEN - Shinta Wurdiana Rhomadona; Dianita Primihastuti (Journal of Midwifery, 2020)
As gestational age increases, the quality of sleep can decrease. It was reported that about 60% of late trimester pregnant women experience fatigue and> 75% experience sleep disturbances. However, these complaints are often ignored, even though it can lead to an increased risk of gestational hypertension, diabetes, prematurity, and postpartum depression. Sleep disturbances can also cause depression and stress that affects the fetus. Mild stress causes an increase in fetal heart rate which, if left untreated, will make the baby hyperactive. Meanwhile, the consequences are depression and babies who are born have less time to sleep deeply. Efforts to overcome this sleep disorder are yoga and lavender aromatherapy inhalation. Purpose: Therefore, the researchers estimated that the application of a combination of prenatal gentle yoga and lavender aromatherapy would be more effective in affecting the quality of sleep in pregnant women, so it is hoped that it can reduce sleep disturbances in third trimester pregnant women. Results: There is a significant effect of the combination of prenatal gentle yoga and inhalation of lavender aromatherapy in improving sleep quality in the treatment group with a value of α = 0.011 or α <0.05. There was a significant difference in the quality of sleep in the group compared to the control group with a value of α = 0.004 or α <0.05. Conclusion: By practicing prenatal gentle yoga and regular inhalation of lavender aromatherapy, it will be able to improve sleep patterns without using sleeping pills which wil